Influence of substrate temperature on the properties of Ag-C films produced by DC Magnetron Sputtering - Calderon, NZ (2018)
Calderon would like to express her thanks to the Fondecyt project number 167-2015 (Concytec, Perú). Pujada express his thanks to the project number FC-F-3-2017, Vicerrectorado de Investigación (UNIPerú), and also to the Universidad de Chile and the Fondecyt Project 1110148 (Conicyt, Chile).